How do the Darmasiswa students learn Indonesian language in Yogyakarta State University, Indonesia? - Wilujeng, Nuning Catur Sri (JOURNAL OF EDUCATION, 2015)
This study was aimed at investigating the language learning strategies(LLSs) employed by students of Indonesian as a foreign language (IFL) at YSU. The study was descriptive analytical. The participants were nine students granted the Darmasiswa (DS) scholarship who undertook their study at YSU. Data were collected using questionnaires and analyzed descriptive qualitatively. Findings of the study showed that (1) the compensation and social LLSs were the highest employed by the students and the memory strategy was the lowest, (2) female students took more od the affective strategy and male students took more of the metacognitive strategy, and (3) there was no inï¬‚ uence of cultural or personal background and nor different level of Indonesian language proï¬ ciency on the application of LLSs